Air Pollution and Cognition in Children: Evidence from National Tests in Denmark - Christina M. Andersen; Jørgen Brandt; Jesper H. Christensen; Lise M. Frohn; Camilla Geels; Timo Hener; Marianne Simonsen; Lars Skipper (CESifo GmbH, 2024)
This paper examines the effects of daily outdoor air pollution variation on student test scores. Using Danish register data for all elementary and lower secondary students, we link home addresses to a 1 km x 1 km pollution grid to measure test day and lifetime pollution exposure. An increase in fine particles (PM2.5) from a very clean to an average day reduces math scores by 1.8% and reading by 0.9% of a standard deviation. Even at low pollution levels, student performance is harmed, especially in math. We find no evidence of heterogeneity by health, socio-economic status, or lifetime exposure.
Keywords: Q53; I21; I18; 330; air pollution; cognition; test scores